W.E.B. Du Bois and His Social-Scientific Research: A Review of His Online Texts - Robert W. Williams (Sociation Today, 2005)
The work of W.E.B. Du Bois which is available online is extensive. Williams provides a scholarly review of the work and life of Du Bois while documenting a very large amount of material available for students and the scholarly community in the online formats